Investigation of laser pulse length and pre-plasma scale length impact on hot electron generation on OMEGA-EP. (2nd February 2017) - Peebles, J; Wei, M S; Arefiev, A V; McGuffey, C; Stephens, R B; Theobald, W; Haberberger, D; Jarrott, L C; Link, A; Chen, H; McLean, H S; Sorokovikova, A; et al.
Abstract: A series of experiments studying pre-plasma's effect on electron generation and transport due to a high intensity laser were conducted on the OMEGA-EP laser facility. A controlled pre-plasma was produced in front of an aluminum foil target prior to the arrival of the high intensity short pulse beam. Energetic electron spectra were characterized with magnetic and bremsstrahlung spectrometers. Pre-plasma and pulse length were shown to have a large impact on the temperature of lower energy, ponderomotive scaling electrons. Super-ponderomotive electrons, seen in prior pre-plasma experiments with shorter pulses, were observed without any initial pre-plasma in our experiment. 2D particle-in-cell and radiation-hydrodynamic simulations shed light on and validate these experimental results.